Publisher Correction: Early preclinical detection of prions in the skin of prion-infected animals - Zerui Wang (Nature Portfolio, 2019)
The original version of this Article contained errors in the author affiliations. Affiliation 2 incorrectly read ‘Department of Neurology, The First Hospital of Jilin University, Changchun 130021 Jilin Province, China.’Affiliation 5 incorrectly read ‘Department of Otolaryngology, The First Affiliated Hospital of Xi’an Jiaotong University, Xi’an 710061 Shanxi Province, China’Affiliation 9 incorrectly read ‘State Key Laboratory for Infectious Disease Prevention and Control, National Institute for Viral Disease Control and Prevention, Chinese Center for Disease Control and Prevention, Beijing 102206, China.’This has now been corrected in both the PDF and HTML versions of the Article.